THE ROLE OF COMPOSITE MATERIALS IN SCIENCE (Conferencea, 2024)
The development of modern technologies creates new materials with high mechanical performance compared to traditional materials, demand for elasticity and other new features. Composite materials based on polymers, ceramics and metals are among the most interesting and promising products. Polymer, ceramic, metal matrix composite materials are used more in engineering, and they are used in the absence of new technology or other materials that respond to production.